426. Use of Real Time IP-10 Measurements to Identify and Monitor the Dysregulated Immune Response in COVID-19 Patients. (31st December 2020) - Lev, Shaul; Gottesman, Tamar; Levin, Gal Shachaf; Ber, Tahel Ilan; Angel, Alon; Kellerman, Lior; Barash, Eran; Navon, Roy; Simon, Einav; Avni, Noa; Hainrichson, Mary; Gottlieb, Tanya; et al.
Abstract: Background: It is estimated that up to 10% of SARS-CoV-2 patients progress from early and pulmonary stages to the most severe stage of illness, which manifests as an extra-pulmonary systemic hyperinflammatory syndrome. Interferon gamma-induced protein 10 (IP-10) is an inflammatory marker that plays a role in the dysregulated host response of COVID-19 infected patients. Clinical monitoring of IP-10 has been restricted in the absence of a rapid diagnostic test. MeMed Key TM is a novel platform recently cleared to provide IP-10 measurements in 15 minutes. We hypothesized that providing physicians with real time IP-10 measurements would support detection and continuous monitoring of patients with a dysregulated immune response and potentially allow personalized immunomodulation to improve patient outcome. IP-10 levels reflect corticosteroid treatment Methods: From 7 th April 2020 to 10 th May 2020 blood was routinely collected serially from 52 SARS-CoV-2 positive patients hospitalized at a COVID-19 dedicated medical center. A clinical decision support protocol was in place focused on managing viral response, oxygenation and inflammatory state (NCT04389645). Results: The median age of the 52 patients was 69, 69% were male, 21% were ventilated, 4 died, 2 due to non-COVID-19 related complications. The most common comorbidities were Diabetes 40% and Hypertension 46%. IP-10 >1000 pg/ml correlated with ICU admission (p< 0.05) and increased COVID-19 severity score (p< 0.01). 19 of the 52 patients had IP-10 >1000 pg/ml, of these 12 were treated with corticosteroids. Monitoring IP-10 within the clinical decision support protocol assisted with personalized corticosteroid regimens with the aim of reducing IP-10 < 1000 pg/ml . The 10 patients that survived exhibited IP-10 levels >1000 pg/ml for 2.6 days on average. In contrast, the 2 patients that died of COVID-19 related complications displayed an average of 7.5 days with IP-10 >1000 pg/ml (p< 0.05). Conclusion: Providing physicians with real time measurements of IP-10 in COVID-19 patients proved a useful tool as part of the clinical decision support protocol. Timely identification, monitoring and personalized treatment of COVID-19 patients exhibiting a dysregulated immune response may aid in improving patient outcome. Further studies are warranted. Disclosures: Tahel Ilan Ber, MD, MeMed (Employee) Alon Angel, n/a, MeMed (Employee) Lior Kellerman, M.D, MeMed (Employee) Eran Barash, MA, MeMed (Employee) Roy Navon, MSc, MeMed (Employee) Einav Simon, PhD, MeMed (Employee) Noa Avni, PhD, MeMed (Employee) Mary Hainrichson, PhD, MeMed (Employee) Tanya Gottlieb, PhD, MeMed (Employee) Kfir Oved, MD, PhD, MeMed (Employee) Eran Eden, PhD, MeMed (Employee)